(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background & Purpose: In developing countries, cervical cancer is the most common gynecological cancer and one of the leading causes of cancer death. Cervical cancers can be prevented through early detection and cervical smear is a sensitive test for it. Materials & Methods: This retrospective study was carried out at Chattagram Maa- Shishu O General Hospital, between July 2012 and June 2013. Total 500 patients were screened having complaints of vaginal discharge, irregular bleeding per vagina, post coital bleeding or something coming out per vagina. History and symptoms along with parity were recorded. Smears were taken by trained Doctor using modified Ayres wooden spatula and plastic endocervical cytobrush which were inserted and rotated 360 over cervix. Both ectocervix and endocervix were sampled. Slides were prepared, labeled, fixed in 95% ethyl alcohol immediately and subsequently stained by pap stain. After staining, slides were mounted with DPX (distren dibutyl phthalate xylene), screened and reported by two Cytopathologist according to The 2001 Bethesda system. Results: Age ranged from 20 to 50 and 50 to75 years with an average age of 37 years. Four hundred sixty five (93%) cases showed inflammatory lesions, 15 (3%) showed atrophy, 8 (1.6%) showed metaplasia and others showed ASCUS, AGUS, LSIL, HSIL, SCC. Eighty percent of all the epithelial abnormalities were found in the age group of 40 years and above. Average age of patients for all the epithelial abnormalities was 49 years. Conclusion: Cervical cancer is one of the most common malignancies in the women of Bangladesh. Pap smear cytology is a useful screening tool to detect pre-invasive cervical epithelial lesions. Based on the findings of this study we recommend at least a single life-time Pap screening cytology of the uterine cervix of all the women aged 40 to 50 years. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19412